Plant 3’ Regulatory Regions From mRNA-Encoding Genes and Their Uses to Modulate Expression - Bernardes, Willian Souza; Menossi, Marcelo (Frontiers in Plant Science, 2020)
Molecular biotechnology has made it possible to explore the potential of plants for different purposes. 3’ regulatory regions have a great diversity of cis-regulatory elements directly involved in polyadenylation, stability, transport and mRNA translation, essential to achieve the desired levels of gene expression. A complex interaction between the cleavage and polyadenylation molecular complex and cis-elements determine the polyadenylation site, which may result in the choice of non-canonical sites, resulting in alternative polyadenylation events, involved in the regulation of more than 80% of the genes expressed in plants. In addition, after transcription, a wide array of RNA-binding proteins interacts with cis-acting elements located mainly in the 3’ untranslated region, determining the fate of mRNAs in eukaryotic cells. Although a small number of 3’ regulatory regions have been identified and validated so far, many studies have shown that plant 3’ regulatory regions have a higher potential to regulate gene expression in plants compared to widely used 3’ regulatory regions, such as NOS and OCS from Agrobacterium tumefaciens and 35S from cauliflower mosaic virus. In this review, we discuss the role of 3’ regulatory regions in gene expression, and the superior potential that plant 3’ regulatory regions have compared to NOS, OCS and 35S 3’ regulatory regions.